2015
DOI: 10.1088/0004-6256/150/3/97
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Radial Velocities in the Old Open Cluster M67 (Ngc 2682). I. Memberships, Binaries, and Kinematics

Abstract: We present results from 13776 radial-velocity (RV) measurements of 1278 candidate members of the old (4 Gyr) open cluster M67 (NGC 2682). The measurements are the results of a long-term survey that includes data from seven telescopes with observations for some stars spanning over 40 years. For narrow-lined stars, RVs are measured with precisions ranging from about 0.1 to 0.8 km s −1 . The combined stellar sample reaches from the brightest giants in the cluster down to about 4 mag below the main-sequence turnof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
243
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(271 citation statements)
references
References 97 publications
(209 reference statements)
21
243
5
2
Order By: Relevance
“…Then we estimate the dynamical mass using the stars velocity dispersion both with he assumption of virial equilibrium and taking into account possible non-stationarity of the cluster and Galactic gravitational field. Note that virial equilibrium is a commonly accepted condition for star clusters (Davies et al 2011, Tofflemire et al 2014, Geller et al 2015. In anticipation of the results, we found that the dynamical (virial) mass is a factor of 5 larger than the luminous mass, and we discuss different possible explanations.…”
Section: Introductionsupporting
confidence: 59%
“…Then we estimate the dynamical mass using the stars velocity dispersion both with he assumption of virial equilibrium and taking into account possible non-stationarity of the cluster and Galactic gravitational field. Note that virial equilibrium is a commonly accepted condition for star clusters (Davies et al 2011, Tofflemire et al 2014, Geller et al 2015. In anticipation of the results, we found that the dynamical (virial) mass is a factor of 5 larger than the luminous mass, and we discuss different possible explanations.…”
Section: Introductionsupporting
confidence: 59%
“…The multiplicative factor 2 is included to scale the mass estimate to the half-mass radius. The value for M 67 has been updated with respect to the van den Berg et al (2013) value, to account for an updated mass estimate (Geller et al 2015). For NGC 6819, new membership information from Platais et al (2011) has been included.…”
Section: Discussionmentioning
confidence: 99%
“…For NGC 6819, new membership information from Platais et al (2011) has been included. References -1 van den Berg et al (2004), Geller et al (2015), 2 Gosnell et al (2012), Platais et al (2013) 3 van den Berg et al (2013), Platais et al (2011) …”
Section: Discussionmentioning
confidence: 99%
“…The best fit age, distance modulus, and reddening value for each set of parameters was then determined using 2-dimensional χ 2 fitting between the points of the M67 CMD (Geller et al, 2015) and the isochrone. Only M67 stars with radial velocity membership probability of 90% or greater were used (from Geller et al, 2015). Allowing the distance modulus, reddening, and age to be free parameters, a χ 2 value for both the magnitude, V, and the color, B − V, was determined for each star in M67.…”
Section: Fitting Isochrones To the Cluster Cmdmentioning
confidence: 99%
“…The cluster has a metallicity around solar, with [Fe/H] = 0.00 ± 0.06 (Heiter et al, 2014) and a reddening of E(B − V) = 0.041 ± 0.004 (Taylor 2007). A color magnitude diagram (CMD) of M67 can be seen in Figure 1 (data from Geller et al, 2015). It is of importance to note that the M67 CMD has a distinctive "hook" feature below the main sequence turn-off.…”
Section: Introductionmentioning
confidence: 99%